The Impact of Brand Image, Quality of Service on Consumer Purchase Behavior for Airlines in Indonesia - Primadi, Andri; Rumondang, Astri; Daulay, Chiara Dharaurah (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2023)
Brand Image and Service Quality are two important concepts in the airline industry that are major in shaping passenger perception and experience. Brand Image is the image or perception owned by an airline in the eyes of consumers or passengers. At the same time, Service Quality shows the extent to which the airline can meet or exceed passenger expectations regarding services provided. This study aims to determine the relationship between service quality and Brand Image in Purchasing Decisions. The study's findings have important implications for airlines in Indonesia as it highlights the importance of maintaining a positive brand image and improving service quality to retain and attract more customers. This research can also guide the aviation industry to improve passenger experience and sustainable business growth. This study used Quantitative methods and Statistical Package for the Social Sciences (SPSS) version 26 to process data from 132 respondents who filled out the questionnaire we distributed. The study reveals that both Brand Image and Service Quality significantly influence Purchasing Decision.